Intelligent decision technologies Proceedings of the 3rd International Conference on Intelligent Decision Technologies (IDT' 2011) - International Conference on Intelligent Decision Technologies 2011 Piraeus, Greece); Watada, J. (Junzo); Phillips-Wren, Gloria; Jain, C.; Howlett, Robert J.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Intelligent Decision Technologies (IDT) seeks an interchange of research on intelligent systems and intelligent technologies which enhance or improve decision making in industry, government and academia. The focus is interdisciplinary in nature and includes research on all aspects of intelligent decision technologies, from fundamental development to the applied system. This volume represents leading research from the Third KES International Symposium on Intelligent Decision Technologies (KES IDT?11), hosted and organized by the University of Piraeus, Greece, in conjunction with KES International. The symposium was concerned with theory, design, development, implementation, testing and evaluation of intelligent decision systems. Topics include decision making theory, intelligent agents, fuzzy logic, multi-agent systems, Bayesian networks, optimization, artificial neural networks, genetic algorithms, expert systems, decision support systems, geographic information systems, case-based reasoning, time series, knowledge management systems, rough sets, spatial decision analysis, and multi-criteria decision analysis. These technologies have the potential to revolutionize decision making in many areas of management, healthcare, international business, finance, accounting, marketing, military applications, ecommerce, network management, crisis response, building design, information retrieval, and disaster recovery for a better future.
From the content: Determining an Efficient Parts Layout for Assembly Cell Production by using GA and Virtual Factory System -- Virtual University -- A New Perspective -- Fuzzy preference based organizational performance measurement -- Software Testing -- Factor Contribution Analysis in a Decision Support Framework
Electronic reproduction.
Keywords: Decision support systems -- Congresses; Decision making -- Data processing -- Congresses; Artificial intelligence -- Congresses